معنى المشكل عند الفقهاء - Abdulaziz bin Muhammad Al-Obaidullah (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2023)
The four schools of jurisprudence were received by the nation with acceptance, and people flew to the horizons with their writings, branches, and fatwas, but like any human effort, they are interspersed with some shortcomings or defects, or something falls into the understanding of its followers that creates the illusion of conflict and confusion between its branches on the one hand and its origins and rules on the other hand. What the meaning is hidden and difficult to understand and comprehend, which is what jurists called “jurisprudential problems.” The problem is the knot of any research, and it is necessary that whoever liberates it and explains it has achieved knowledge, since clarification occurs by removing the thing from the space of the problem into the space of manifestation.” Since the people who raise the issue are the scholars of the sects who are the most knowledgeable about their origins and branches, these issues have their importance and status. Jurists need to track down these problem areas, and examine proven solutions or find appropriate solutions for them, among the important skills that are useful to the student of jurisprudence, which requires the use of mind, long-sightedness, and deliberation. I have concluded that the concept of the problem according to the jurists means “a jurisprudential text whose meaning is ambiguous or contradicts an established principle according to the estimation of the problem person, and which can be corrected.”